Epidemiological characteristics and influencing factors of hand, foot and mouth disease reinfection cases in Jiulongpo District, Chongqing, China, 2009–2023 - Zhou, Huixian; Yao, Yuan; Long, Qianjin; Deng, Chunyan (Frontiers in Public Health, 2025)
ObjectiveTo analyze the epidemiological characteristics of Hand, Foot and Mouth Disease (HFMD) reinfection and its influencing factors in Jiulongpo District from 2009 to 2023 to provide targeted prevention and control recommendations for key factors.MethodsHFMD cases in Jiulongpo District of Chongqing were derived from the China Information System for Disease Control and Prevention from 2009 to 2023. Descriptive analysis was used to analyze the epidemiological characteristics of HFMD reinfection, spatial autocorrelation to analyze the regional clustering, and binary logistic regression to analyze the influencing factors.ResultsFrom 2009 to 2023, 4,764 HFMD reinfection cases involving 2,436 individuals were reported in Jiulongpo District, with a reinfection rate of 5.48%. The interval between the two infections ranged from 26 to 3,863 days, and 71.51% of patients were reinfected within 2 years. There was a bimodal distribution in time (April–July and October–November). In the population, the reinfection rate was 5.87% in males and 4.93% in females, 3.97% in scattered children and 7.89% in kindergarten children, 8.61% in children >3 years old, and 4.68% in children ≤3 years old. There was a spatial positive correlation of HFMD reinfection in Jiulongpo District, with hot spots concentrated in the rural area and cold spots in the urban area. The multifactorial logistic regression analysis showed that reinfection risk was higher in non-epidemic years, male, rural areas, >3 years old, and kindergarten children (p < 0.05).ConclusionPost-epidemic prevention and control measures should prioritize interventions to target reinfection, focusing on children in rural areas and kindergartens. Improve rural infrastructure and sanitation, raise disease awareness in kindergartens, train healthcare workers, and promote hygiene to reduce HFMD reinfection.